2007
DOI: 10.1002/ccd.21023
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study to evaluate the safety and feasibility of intracoronary CD133+ and CD133 CD34+ cell therapy in patients with nonviable anterior myocardial infarction

Abstract: Intracoronary infusion of selected CD133(+) and CD133(-)CD34(+) progenitor cells to a previously infarcted and nonviable anterior wall is safe, and results in sustained improvement in segmental myocardial perfusion and in favorable left ventricular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 40 publications
(39 reference statements)
1
41
0
4
Order By: Relevance
“…Particularly autologous CD34 ϩ or CD133 ϩ stem/ progenitor cells have been therapeutically transplanted in patients with severe ischemic heart or limb diseases, and these initial clinical experiences indicate the safety and feasibility as well as the effectiveness of cell-based therapy [3,[11][12][13][14][15][16][17][18][19].…”
Section: Several Translational Researchers Have Demonstrated That Cd34mentioning
confidence: 99%
“…Particularly autologous CD34 ϩ or CD133 ϩ stem/ progenitor cells have been therapeutically transplanted in patients with severe ischemic heart or limb diseases, and these initial clinical experiences indicate the safety and feasibility as well as the effectiveness of cell-based therapy [3,[11][12][13][14][15][16][17][18][19].…”
Section: Several Translational Researchers Have Demonstrated That Cd34mentioning
confidence: 99%
“…When comparing the DanCell study to other studies similar in design and demographics, no significant increase in LVEF was found in DanCell, while other studies have been able to show this [4,7,8,9,10,11]. In DanCell, the evaluation of LVEF was performed in a blinded setting, thus excluding bias.…”
Section: Discussionmentioning
confidence: 99%
“…In the two randomized controlled trials using intramyocardial injection of stem cells, improvement in LVEF was shown [7,11] and one showed improvement in mortality [7]. The rest of the comparable studies all used intracoronary administration, and these also seem to have a positive outcome [4,8,9,10]. On the basis of the current limited data, a recent meta-analysis found that intramyocardial injection may be superior to intracoronary infusion in patients with LV systolic dysfunction [3].…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study indicated that early intracoronary administration of haematopoietic BMMCs in patients with previous myocardial infarction was associated with accelerated luminal loss and reduced conductance of the infarct-related artery. 18 Manginas et al 19 …”
Section: Safetymentioning
confidence: 99%